Program Bandung Menjawab sebagai Implementasi Humas Digital Kota Bandung - Ridha Rihadatul'aisy; Ani Yuningsih (UNISBA Press, 2024)
Abstract. An institution cannot be separated from the dynamics of the issues at hand. Issue management is necessary to address such dynamic conditions. The shift of various information technology mediums that were previously conducted conventionally has now transitioned to using digital media. This has been utilized by the Communication and Information Agency (Diskominfo) of Bandung City to manage issues related to various programs and policies of the Bandung City government through the